2021
DOI: 10.1111/tct.13393
|View full text |Cite
|
Sign up to set email alerts
|

PLUS Framework: guidance for practice educators

Abstract: Summary Background The practice educator role is complex and becoming more so with changes in placement configurations since the COVID‐19 pandemic. The role requires practitioners to manage clinical activities while providing learning opportunities and supervision for students. This can be time‐consuming in often stretched clinical settings. This research investigated how experienced practice educators in occupational therapy tailored their approach to supporting student learning to make the most of limited su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Therefore, developing an awareness about the varied sources of discipline-specific and related knowledge from which practice educators draw to inform their reasoning and decision-making is a useful first step. The Professional Learning through Useful Supports (PLUS) Framework (Dancza et al, 2021) focuses on guidance strategies for practice educators to support students’ learning on placement. The PLUS Framework identifies the value of practice educators reflecting on their own theory-to-practice links to enable them to make intuitive decisions explicit as they articulate and model their own use of theory in practice (Dancza et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, developing an awareness about the varied sources of discipline-specific and related knowledge from which practice educators draw to inform their reasoning and decision-making is a useful first step. The Professional Learning through Useful Supports (PLUS) Framework (Dancza et al, 2021) focuses on guidance strategies for practice educators to support students’ learning on placement. The PLUS Framework identifies the value of practice educators reflecting on their own theory-to-practice links to enable them to make intuitive decisions explicit as they articulate and model their own use of theory in practice (Dancza et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The Professional Learning through Useful Supports (PLUS) Framework (Dancza et al, 2021) focuses on guidance strategies for practice educators to support students' learning on placement. The PLUS Framework identifies the value of practice educators reflecting on their own theory-to-practice links to enable them to make intuitive decisions explicit as they articulate and model their own use of theory in practice (Dancza et al, 2021).…”
Section: Educational Knowledge Solutionsmentioning
confidence: 99%
“…The Professional Learning through Useful Support (PLUS) Framework aims to address this gap through guiding supervisors in optimising educational opportunities for students (Dancza et al, 2021). The PLUS Framework presents a practical approach for supervisors to consider their teaching strategies, making explicit connections between theory and practice, while challenging students to learn and grow.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The PLUS Framework presents a practical approach for supervisors to consider their teaching strategies, making explicit connections between theory and practice, while challenging students to learn and grow. It places the students' learning at the core of the Framework and is structured around three primary focal points: guiding learning, making explicit the connections between theory and practice, and supportively challenging students (Dancza et al, 2021; Figure 1). Previous studies in the United Kingdom have shown that providing students with time and opportunities for experiential learning, including learning from both successful outcomes and mistakes in a supervised setting, enhances their confidence and competence (Dancza et al, 2019(Dancza et al, , 2021.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation